Common variable immunodeficiency in two kindreds with heterogeneous phenotypes caused by novel heterozygous NFKB1 mutations - Staels, Frederik; De Keukeleere, Kerstin; Kinnunen, Matias; Keskitalo, Salla; Lorenzetti, Flaminia; Vanmeert, Michiel; Prezzemolo, Teresa; Pasciuto, Emanuela; Lescrinier, Eveline; Bossuyt, Xavier; Gerbaux, Margaux; Willemsen, Mathijs; et al. (Frontiers in Immunology, 2022)
NFKB1 haploinsufficiengcy was first described in 2015 in three families with common variable immunodeficiency (CVID), presenting heterogeneously with symptoms of increased infectious susceptibility, skin lesions, malignant lymphoproliferation and autoimmunity. The described mutations all led to a rapid degradation of the mutant protein, resulting in a p50 haploinsufficient state. Since then, more than 50 other mutations have been reported, located throughout different domains of NFKB1 with the majority situated in the N-terminal Rel homology domain (RHD). The clinical spectrum has also expanded with possible disease manifestations in almost any organ system. In silico prediction tools are often used to estimate the pathogenicity of NFKB1 variants but to prove causality between disease and genetic findings, further downstream functional validation is required. In this report, we studied 2 families with CVID and two novel variants in NFKB1 (c.1638-2A>G and c.787G>C). Both mutations affected mRNA and/or protein expression of NFKB1 and resulted in excessive NLRP3 inflammasome activation in patient macrophages and upregulated interferon stimulated gene expression. Protein-protein interaction analysis demonstrated a loss of interaction with NFKB1 interaction partners for the p.V263L mutation. In conclusion, we proved pathogenicity of two novel variants in NFKB1 in two families with CVID characterized by variable and incomplete penetrance.